ATM lane simulator / Ching Kim Joo - Ching, Kim Joo (2001)
This project describes the development of ATM Local Area Network Emulation (LANE) simulator components. In LANE, an A TM network is configured to simulate an Ethernet or token ring network and coexist with the legacy network without making any modification to Them.The development of this simulator incorporates several important features. The most important feature of the simulator is that it is build based on object-oriented approach, which is able to provide the benefits of re usability, flexibility and extensibility. The second important feature is that it supports multi threaded operations. This means that every object able to act simultaneously. Besides that, the simulator is web-enabled, which means the simulator can be accessed from the Internet and thus increase the usability of the network simulator. This network simulator can helps user to understand the operation of LANE and provides the benefits of testing the network without making any investment on the real network.Thus,it can save the cost in terms of unnecessary restructuring for experimentation. Further research on LANE can be carried out with this simulator.